Effects of synthetic media and epigenetic regulators on secondary metabolites production by soil fungi / Siti Nur Atiqah Mohd Ghani - Mohd Ghani, Siti Nur Atiqah (2013)
The type of culture media and the presence of epigenetic regulators affect the production of secondary metabolites by fungi. In general, most of the tested fungi produce more secondary metabolites when cultured in natural media (PDB) than synthetic media (Czapek). A greater amount of metabolites are also produced when 100% concentration of media is used instead of at reduced strength. With the presence of epigenetic regulators, different fungi respond differently towards them. Some of them are affected and results an addition or reduction in the amount of secondary metabolite produced while some of them do not give any respond and show no changes in the secondary metabolites profile as compared to control sample. This support the concept of using a series of media and growth conditions to explore the fungal secondary metabolism in a controlled and extensive manner.